2016
DOI: 10.1016/j.rppnen.2015.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Superior lung capacity in swimmers: Some questions, more answers!

Abstract: Swimmers had statistically higher values of VC, FVC, FEV1 and FEV1/FVC when compared to both the football players and the controls, as the latter two showed no in-between differences. There was significant positive correlation between age, body weight and body height and each of the above named pulmonary parameters, when presented separately for swimmers, football players and the control group. When controlled for the anthropometric features, larger lung volumes in swimmers were not influenced by training peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
0
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 13 publications
5
25
0
4
Order By: Relevance
“…Therefore, the authors suggested that besides height, other factors could have impact upon lung function such as fat free mass, thoracic diameter, and trunk length. [13,23] The present study shows that at maximal exercise, the swimmers and field sports group reached similar V̇O2 peak, ̇ , and workloads, all of which were significantly greater than the recreational group (Table 3). Despite these differences it was found that their ventilatory reserve (̇ expressed as a percent of MVV) were the same at around 20%.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Therefore, the authors suggested that besides height, other factors could have impact upon lung function such as fat free mass, thoracic diameter, and trunk length. [13,23] The present study shows that at maximal exercise, the swimmers and field sports group reached similar V̇O2 peak, ̇ , and workloads, all of which were significantly greater than the recreational group (Table 3). Despite these differences it was found that their ventilatory reserve (̇ expressed as a percent of MVV) were the same at around 20%.…”
Section: Discussionsupporting
confidence: 54%
“…Whether the different lung volumes and capacities reported in swimmers is due to their training, the result of a genetic predisposition, or a mixture of both, has been investigated in other studies. [11,13,20,27] In support of the importance of genotype, it has been reported that swimmers tend to be taller than age and weight matched peers, and that these anthropometric characteristics are influenced by genetic inheritance. [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One could interpret these findings as additional evidence that overweight promotes a lung growth that is different from normal, with a disproportional increase in lung parenchyma (FVC) in comparison to airway (maximal flows and airway resistance). The same pattern of large lungs is seen in swimmers ( 36 ), divers ( 37 ), and other such athletes, as well as subjects living in high altitudes ( 38 ), and these are findings that have no association with respiratory disease. These observations recommend caution to label a lower FEV 1 /FVC as a true obstructive pattern in overweight children.…”
Section: Discussionmentioning
confidence: 67%
“…Some recent scientific research observed that some particular sport disciplines improve the lung function and the cardiovascular capacity better than others, these include swimming, and, as recently reported, basketball, water polo and rowing (Lazovic et al, 2015;Bougault et al, 2009;Vaithiyanadane et al, 2012). Also swimmers achieve larger lung volumes and higher functional cardiorespiratory system capacity compared to other athletes (Lazovic-Popovic et al, 2016).…”
Section: Introductionmentioning
confidence: 97%